Chitinase 3-like protein 1: a diagnostic biomarker for early liver fibrosis in autoimmune liver diseases - Liu, Shafei; Peng, Conggao; Xia, Shijia; Li, Chaonan; Dai, Xiahong; Liu, Xingyu; Zhang, Meng; Li, Xiaoping; Tang, Lingling (Frontiers in Immunology, 2025)
Background and AimsChitinase 3-like protein 1 (CHI3L1) is a marker of liver fibrosis produced mainly by hepatic macrophages. However, few studies have assessed the relationship between CHI3L1 and liver fibrosis in autoimmune liver diseases (AILDs). We aimed to explore the diagnostic value of CHI3L1 for liver fibrosis in AILDs and to compare its application differences between AILDs and chronic hepatitis B (CHB) patients.MethodsThe fibrotic group was defined as liver stiffness measurement (LSM) > 9.70kPa. Serum CHI3L1 levels were measured by ELISA in 78 AILDs patients, 65 chronic hepatitis B patients. The diagnostic accuracy was evaluated by the area under the receiver operating characteristic curve (AUROC).ResultsSerum CHI3L1 levels in AILDs patients were positively correlated with LSM (r=0.750, p <0.001). The AUROC for serum CHI3L1 in identifying significant liver fibrosis was 0.939 (95% CI: 0.891 - 0.988), which was higher than that of other non - invasive fibrosis scores (APRI, FIB - 4, GPR, AAR, NLP, and PLR). At the optimal cutoff value of 86.84 ng/mL, the sensitivity and specificity were 92.9% and 83.3%, respectively. Furthermore, in patients with no significant difference in LSM, serum CHI3L1 levels were higher in the autoimmune liver disease group than in the CHB group.ConclusionSerum CHI3L1 is an effective non-invasive indicator for assessing liver fibrosis in AILDs patients and may vary in different etiologies.